2005
DOI: 10.1093/ps/84.11.1763
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics and sperm production of turkey semen in relation to strain and age of the males

Abstract: The effect of turkey strain [BUT (Big-6), Hybrid Large White (HLW), and Nicholas (N-700)] on semen quantitative parameters (ejaculate volume, sperm concentration, and total number of sperm) and biochemical parameters (seminal plasma protein concentration, acid phosphatase activity in spermatozoa and seminal plasma, and antiproteinase activity of seminal plasma) was investigated over the reproductive period. The Big-6 strain had better quantitative parameters of semen compared with HLW and N-700 strains. Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…The fertility and hatchability of crosses between white and black plumage indigenous turkeys obtained were favourably compared with those reported by Kotlowska et al (2005) who reported an average percentage fertility value of 94.51% for Hybrid Large White Nicholas. The percentage hatchability recorded in this study was not affected by plumage colour.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The fertility and hatchability of crosses between white and black plumage indigenous turkeys obtained were favourably compared with those reported by Kotlowska et al (2005) who reported an average percentage fertility value of 94.51% for Hybrid Large White Nicholas. The percentage hatchability recorded in this study was not affected by plumage colour.…”
Section: Discussionmentioning
confidence: 52%
“…Some semen quality parameters are characterized in terms of volume, colour, concentration, motility, mass activity, viability, and morphology. The parameters vary with the age of males in all poultry species leading to a reduction in fertility as the birds grows older (Kotlowska et al, 2005), but evaluation of semen quality parameters based on plumage colour has not been properly documented. Fertility is a complex interaction of traits involving two individuals (male and female) of different genetic composition and their ability to mate and produce viable offspring (Foote, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(British United Turkeys Big 6, Grelier, Saint-Laurent-de-la-Plaine, France) maintained under standard husbandry conditions at the Turkey Testing Farm of the Department of Poultry Science (University of Warmia and Mazury in Olsztyn, Poland) as described in detail ( Słowińska et al, 2020 ). The sampling time was chosen within reproductive season – the 8th week of reproduction season, when a high quality semen is produced ( Kotłowska et al, 2005 ). Only bird producing high quality semen were chosen for experiment, as shown by Słowińska et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…A concentração espermática varia entre 592 a 812x10 6 espermatozoides/mL e o volume do ejaculado de 0,020 a 0,035mL (Chelmonska et al, 2008). Em galos, a produção diária é de 173x10 6 sptz/g/dia e a concentração é de 6,17x10 9 espermatozoides/mL e o volume do ejaculado de 0,19mL (Bath;Chaudhari 2002;Maciel et al, 2008) e nos perus é de 6,54x10 9 espermatozoides/mL e volume de 0,35mL (Kotlowska et al, 2005).…”
Section: Anatomia E Fisiologia Do Machounclassified